The Construction of the National Identity of the Israelites from the Perspective of Geographical Space Changes in the Book of Ruth - ZHAO, Liangqin (Journal of Research for Christianity in China (JRCC), 2025)
The Book of Ruth, as a short narrative in the Hebrew Bible, through the story of Ruth, a Moabite woman, migrating and integrating into the Israelite community, demonstrates the profound connection between geographical space changes and the construction of national identity. This article takes geographical space as the entry point, combining textual analysis, historical sociology, and cultural geography theories, to explore how the geographical space transformation from Moab to Bethlehem in the Book of Ruth symbolizes the crossing and reconstruction of the boundaries of the Israelite national identity. The Book of Ruth, through the fluidity and openness of geographical space, challenges the exclusive narrative of the traditional Israelite ethnic group, emphasizes the identity recognition model centered on moral law, and provides a model for identity integration for the Israelite community in the diaspora period.